2018
DOI: 10.1590/0034-7167-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Being caregiver of people with Parkinson's Disease: experienced situations

Abstract: Objective: To understand the experience of caring for a person with Parkinson's Disease. Method: We used the qualitative study and thematic analysis with family caregivers of people with Parkinson's Disease. Results: Three thematic categories were identified, being: Feelings related to Parkinson's Disease; Changes in family daily routines; Caregiver strategies for self-care. Final considerations: Family care has shown the need for health services to provide caregivers support, as they experience situations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
0
12
0
6
Order By: Relevance
“…This feeling can lead to disorders both in the personal and in the family, leading to a wear and unbalance of relationships, as well as damage to the attention given to the sick subject. 17,18 Thus, it is observed that the care routine for a dependent individual is permeated by multiple and ambiguous feelings, love, dedication, anger, sadness, fear and worry. It is worrying that negative feelings, when present for a long period, can cause intense wear on the caregiver's ability to play their role with quality, and it is essential the performance of professionals who value and welcome the wishes presented.…”
Section: Discussionmentioning
confidence: 99%
“…This feeling can lead to disorders both in the personal and in the family, leading to a wear and unbalance of relationships, as well as damage to the attention given to the sick subject. 17,18 Thus, it is observed that the care routine for a dependent individual is permeated by multiple and ambiguous feelings, love, dedication, anger, sadness, fear and worry. It is worrying that negative feelings, when present for a long period, can cause intense wear on the caregiver's ability to play their role with quality, and it is essential the performance of professionals who value and welcome the wishes presented.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation points out that 68% of informal caregivers present the Burnout Syndrome -professional fatigue due to the stress that is experienced. This condition causes severe consequences for the individual's health, emanating from the loss of quality of life and the physical, psychological and social well-being (13) . Besides the work overload of activities performed by the caregiver, there is also the emotional grieve, because the caregivers tend to neglect their own needs on behalf of the patient (14) .…”
Section: Discussionmentioning
confidence: 99%
“…Existe um consenso na literatura sobre a importância do papel do cuidador como apoio oferecido pelos serviços de saúde e sociais 9,10,11,12,1,14,15,16,17 . Ainda é possível afirmar que em todos os estudos foi possível perceber na maioria dos cuidadores a presença do estresse e que ainda uma grande maioria privou-se de momentos de lazer sacrificando sua rotina pessoal fragilizando sua saúde física, emocional e social 9,10,11,12,13,14,15,16,17…”
Section: Materiais E Métodosunclassified